Analisis Pengelolaan Keuangan Desa Dalam Memaksimalkan Efisiensi Belanja Biaya Pembangunan Desa Babakan Kab. Purwakarta - Purwana, Edi; Putri Utami, Indri; Izzati, Nur; MS, Paojan (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This study aims to analyze the effect of village financial management on the efficiency of development expenditure in Babakan Village, Wanayasa District, Purwakarta Regency. Good financial management is a crucial prerequisite to ensure that development budgets are used effectively, transparently, and accountably. This research explores four main aspects of village financial management: planning, implementation, bookkeeping, and reporting. A quantitative approach is applied, using questionnaires distributed to village officials and community members directly involved in development programs. The data is analyzed using simple linear regression to determine the extent of the effect of financial management variables on development expenditure efficiency. The research findings indicate that the implementation of village financial management strategies, including careful budget planning, increased transparency, and community participation, as well as strengthened internal supervision and control, has a positive impact on enhancing the efficiency of village development spending. The study concludes that the better the village’s financial governance, the more efficient the realization of development spending. The study recommends improving the human resource capacity of village officials through financial management training and utilizing information technology to enhance financial accountability processes.